Оценка уровня коммерческой привлекательности объектов интеллектуальной собственности - Косенко, Александра Петровна (Университетская книга, 2013)
Рассмотрены подходы к оценке уровня коммерческого потенциала объектов интеллектуальной собственности. Проанализированы возможности использования для этой цели традиционных подходов к определению экономической эффективности интеллектуального бизнеса. Разработаны предложения оценки уровня коммерческой привлекательности интеллектуального продукта с использованием концепции технологического рычага.

Going is considered near the estimation of level of commercial potential of objects of intellectual property. Possibilities of the use are analyzed for this purpose of the traditional going near determination of economic efficiency of intellectual business. Suggestions of estimation of level of commercial attractiveness of intellectual product are developed with the use of conception of technological lever.
Estimation of level of commercial attractiveness of objects of intellectual property
Keywords: технологический аудит; экономическая эффективность; коммерческий потенциал; технологический рычаг; technological audit; economic efficiency; commercial potential; technological lever